Triumph of the commons : Wikia and the commercialization of open-source communities in 2009 - Greenstein, Shane M., (SAGE Knowledge. Cases., 2017)
In 2009 Wikia was the Internets largest for-profit provider of hosted open-source wikis, with over a million daily users. After five years of existence, the organization had supported a wide range of exploratory activities, experiencing both success and failure. With approximately $3 million of cash on hand, Wikia turned cash flow positive in 2009, with revenues of approximately $4.5 million, affording it time and flexibility to try new things. Some of the companys employees and investors suggested that Wikia should attempt to expand and market itself more aggressively, but which strategic direction should receive priority? The case presents many of the issues and tradeoffs facing CEO Gil Penchina as he formulates these priorities.